Assessing the Moisture and Aging Susceptibility of Cold Mix Asphalt Concrete (Journal of Engineering, 2021)
Laboratory experience in Iraq with cold asphalt concrete mixtures is very limited. The design and use of cold mixed asphalt concrete had no technical requirements. In this study, two asphalt concrete mixtures used for the base course were prepared in the laboratory using conventional cold-mixing techniques to test cold asphalt mixture (CAM) against aging and moisture susceptibility. Cold asphalt mixtures specimens have been prepared in the lab with cutback and emulsion binders, different fillers, and curing times. Based on the Marshal test result, the cutback proportion was selected with the filler, also based on the Marshal test emulsion. The first mixture was medium setting cationic emulsion (MSCE) as a binder, hydrated lime, and ordinary portland cement as a filler (7.95% MSCE + 2%HL + 3% OPC). The second mixture used was medium curing cutback (MC-250) as a binder and ordinary portland cement as a filler (5.18% MC 250 + 5% OPC). The indirect tensile strength (ITS) of the samples was measured at 25 ° C. It was found that the cold mix with the MSCE binder had a high ITS value relative to the cold mix with the cutback asphalt binder (MC-250). The dry mixture of MSCE  ITS was approximately 3.77 times the dry mixture of MC-250. The MSCE wet mix was about 4.2 times the wet MC-250 mix. Tensile strength ratio result (TSR %) for the MSCE binder mix and the cutback MC-250 binder mix showed that the MSCE mix has a reasonable moisture resistance (77% ) compared to the MC-250 mix (69.2 %). The aging test and aging ratio result showed that asphalt binder oxidation has a significant effect on age-related pavement degradation as it changes the time-temperature relationship depending on the viscoelastic properties of the asphalt binder. The result clearly showed that the MSCE binder mix had a high resistance to aging (440 Kpa) compared to the cutback (MC-250) binder mix (110 Kpa). In contrast, the MSCE aging ratio (90 %) was higher than the MC-250 ratio (85 %).